2017
DOI: 10.1016/j.celrep.2017.07.077
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Immunogenicity of Native-like HIV-1 Envelope Trimers by Hyperstabilization

Abstract: SummaryThe production of native-like recombinant versions of the HIV-1 envelope glycoprotein (Env) trimer requires overcoming the natural flexibility and instability of the complex. The engineered BG505 SOSIP.664 trimer mimics the structure and antigenicity of native Env. Here, we describe how the introduction of new disulfide bonds between the glycoprotein (gp)120 and gp41 subunits of SOSIP trimers of the BG505 and other genotypes improves their stability and antigenicity, reduces their conformational flexibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
220
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 158 publications
(236 citation statements)
references
References 38 publications
16
220
0
Order By: Relevance
“…The resultant soluble trimers, of BG505 and other genotypes, have a native‐like structure as judged by multiple criteria including negative‐stain electron microscopy (NS‐EM), and they present epitopes for multiple bNAbs but few for non‐neutralizing antibodies (non‐NAbs) (Julien, Cupo, et al, ; Lyumkis et al, ; Pancera et al, ; Sanders et al, ; Sanders & Moore, ; Ward & Wilson, ). Several stability and/or antigenicity improvements to the prototypic BG505 SOSIP.664 trimer have since been described (Chuang et al, ; de Taeye et al, ; Ringe, Ozorowski, et al, ; Sanders & Moore, ; Torrents de la Pena et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The resultant soluble trimers, of BG505 and other genotypes, have a native‐like structure as judged by multiple criteria including negative‐stain electron microscopy (NS‐EM), and they present epitopes for multiple bNAbs but few for non‐neutralizing antibodies (non‐NAbs) (Julien, Cupo, et al, ; Lyumkis et al, ; Pancera et al, ; Sanders et al, ; Sanders & Moore, ; Ward & Wilson, ). Several stability and/or antigenicity improvements to the prototypic BG505 SOSIP.664 trimer have since been described (Chuang et al, ; de Taeye et al, ; Ringe, Ozorowski, et al, ; Sanders & Moore, ; Torrents de la Pena et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…When tested as immunogens in rabbits, guinea pigs and macaques, the original and improved versions of SOSIP.664 trimers of various genotypes induce a narrow‐specificity neutralizing antibody (NAb) response against the autologous Tier‐2 (i.e., neutralization‐resistant) virus, together with NAbs to Tier‐1 (i.e., neutralization‐sensitive) viruses (Cheng et al, ; Chuang et al, ; de Taeye et al, ; Klasse et al, ; Sanders & Moore, ; Sanders et al, ; Torrents de la Pena et al, ). The latter antibodies are predominantly directed against the V3 region of gp120, and their titers can be reduced by engineering variant trimers to suppress the immunogenicity of this region (Chuang et al, ; de Taeye et al, ; Ringe, Ozorowski, et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypervariable V3 loop of gp120, which is concealed in a closed trimer, is immunodominant and elicits antibodies that can only neutralize autologous tier 1 viruses. Several very recent studies have revealed ways of eliminating elicitation of such antibodies, which distract the immune system from the production of the relevant bNAbs, by further stabilization of the recombinant Env trimer ectodomain by structure guided mutagenesis (de Taeye et al, 2015;Joyce et al, 2017;Kulp et al, 2017;Torrents de la Peñ a et al, 2017). Furthermore, recent experiments immunizing rabbits with a SOSIP version of a transmission founder virus succeeded in eliciting antibodies neutralizing heterologous tier 2 viruses, but only with the engineered version that stabilized the closed form and did not expose the V3 loop (Saunders et al, 2017).…”
Section: Undesirable Antibodies Directed Against the V3 Loop Of Hiv Envmentioning
confidence: 99%
“…The abundances of oligomannose-type glycans of so far characterized soluble, recombinant, trimeric Env mimics such as e.g. BG505 SOSIP.664, BG505 SOSIP.v4.1, B41 SOSIP.664 and AMC008/11 SOSIP.664 typically range from ~60 % to ~70 % [18,19,2429]. The most prominent structure is usually the most underprocessed glycan Man 9 GlcNAc 2 with a relative abundancy of ~20 % to ~40 % compared to other glycoforms (Figure 2B).…”
Section: Global Profiling Of the Overall Env Glycosylation Fingerpmentioning
confidence: 99%